Clinical implications of the blood urea nitrogen/creatinine ratio in heart failure and their association with haemoconcentration - Sujino, Yasumori (ESC Heart Fail, 2019)
AIMS: The blood urea nitrogen (BUN)/creatinine ratio is a strong prognostic indicator in patients with acute decompensated heart failure (ADHF). However, the clinical impact of a high BUN/creatinine ratio at discharge with respect to renal dysfunction, neurohormonal hyperactivity, and different responsiveness to decongestion therapy remains unclear. Herein, we examined (i) the predictive value of a high BUN/creatinine ratio at discharge and (ii) its haemoconcentration‐dependent effects, in patients with ADHF. METHODS AND RESULTS: The West Tokyo Heart Failure registry was a multicentre, prospective cohort registry‐based study that enrolled patients hospitalized with a diagnosis of ADHF. The endpoint was post‐discharge all‐cause death. Based on the degree of haemoconcentration, patients (n = 2090) were divided into four subcategories. In multivariate proportional hazard analyses, a higher BUN/creatinine ratio was independently associated with higher all‐cause mortality in the total population and in the extreme haemodilution (ΔHaemoglobin ≤ −0.9 g/dL) and haemoconcentration (0.8 g/dL ≤ ΔHaemoglobin) subcategories, but not in the modest haemodilution/haemoconcentration subcategories. CONCLUSIONS: A higher BUN/creatinine ratio at discharge was independently associated with higher post‐discharge all‐cause mortality in patients with ADHF. The predictive value of a high BUN/creatinine ratio at discharge was haemoconcentration dependent and may be an unfavourable predictor in patients showing excessive haemoconcentration and haemodilution, but not in those showing modest haemoconcentration/haemodilution.